Assessment of behavior and barriers of post-exposure prophylaxis for prevention of rabies in patients attending a tertiary care center in eastern India – a mixed method approach - Debata, Ipsita; Nayak, Smrutiranjan; Behera, Basanta Kumar; Panda, Prem Sagar; Nayak, Rosy; Mandal, Dibyajyoti (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Rabies from animal bites, although preventable, is almost 100% fatal, with the dog being the most common infected animal. Several factors influence the timely initiation of post-exposure prophylaxis (PEP) which needs to be explored. This study aimed to determine the facilitating and inhibiting factors in initiating PEP among animal bite victims attending a tertiary care center in Eastern India. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A cross-sectional study was conducted among 150 consenting animal bite victims attending casualty and medicine as out-patients in a tertiary care hospital. A mixed-method study approach was undertaken to explore the facilitating and inhibiting factors for the timely initiation of PEP using a pre-tested and semi-structured questionnaire and in-depth interviews. Data were analyzed using SPSS software version 20. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The most common biting animal were dogs (96.2%). Around 102 patients (68%) were males and 48 (32%) were females. Timely initiation of PEP was seen in 112 (74.7%) of the study sample while delay was seen in 38 (25.3%). The inhibiting factors were the absence of an accompanying person (54.67%), the absence of vaccines and immunoglobulins in the nearest health facility (50.67%), referral from other health facilities (44%) and preferred other modalities of treatment (24.67%). Delays in initiation of PEP was significantly associated with gender (p=0.018), place of residence (p<0.001), those living more than 20 km from a health facility (p=0.014), educational status (p<0.001), and those with monthly income <10000 INR (p<0.01). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Lower economic status, education, and accessibility to health facilities were major inhibiting factors causing a delay in the initiation of PEP. Further, community-based studies are warranted.